PRODUCTION AND ESTIMATION OF METHANE EMISSIONS FROM COWS FED WITH SMALL-GRAIN CEREALS IN THE CENTRAL HIGHLANDS OF MEXICO - Jesús Israel Vega-García; Felipe López González; Ernesto Morales-Almaraz; Carlos Manuel Arriaga-Jordán (Tropical and Subtropical Agroecosystems)
Background: Given the demand for meat and milk, it is necessary to increase the productivity of ruminant animals, nevertheless livestock also contributes to climate change due to annual methane (CH4) emissions, having a detrimental effect on the atmosphere, due to its effect greenhouse and also represents a loss of dietary energy for ruminant animals. Objective: The objective was to evaluate the nutritional quality in vitro, as well as the production and estimation of methane of small grain cereals in small-scale milk production systems, through two experiments. Methodology: In experiment 1, twelve dairy cows were compared through continuous grazing (6 h/d) in a 3x3 Latin square design, replicated three times with three 14-d experimental periods and three small-grain cereals: rye (Secale cereale) (CEN), wheat (Triticum aestivum) (TRG) and triticale (Triticosecale Witt.) (TRT), in addition the cows were supplemented with 4.5 kg DM/cow/d of commercial concentrate. In experiment 2, six cows grazing continuously (8 h/d) on a kikuyu grass (Cenchrus clandestinus) pasture were used in a double reversible design with the inclusion of 10 kg DM of rye silage (ECE) or rye silage. triticale (ETR), in addition the cows were supplemented with 3.6 kg DM/cow/d of commercial concentrate; this experiment also had three 14-d experimental periods. Forage (for chemical composition) and milk samples were taken at the end of each experimental period. Results: In experiment 1, the nutritional composition presented a high quality (mean of 145 and 740 g/kg DM, for CP and IVDMD, respectively), on the other hand, for experiment 2 the quality was medium-low (mean of 76 and 653 g/kg DM, for CP and IVDMD, respectively) regarding the fermentation parameters obtained through the in vitro gas production technique, as well as the methane production of the forages and the estimation of enteric CH4 production. No significant differences (P>0.05) were detected between the evaluated treatments. Implications: The results of this work provide information on the role that small grain cereals can play in methane emissions, in these production systems according to their nutritional value. Conclusions: in Experiment 1, it is concluded that rye, wheat and triticale are viable options to obtain medium-quality forage suitable for grazing, presenting enteric methane emissions, as well as moderate emission intensity, similar to those produced by quality pasture grazing. Regarding Experiment 2, both rye silage and triticale silage are presented as options to be used in these milk production systems in winter, without greatly increasing enteric methane emissions.